PENINGKATAN KOMPETENSI SDM DALAM PENGEMBANGAN KAMPUNG BATIK SOKARAJA KULON SEBAGAI DESTINASI WISATA BERBASIS BUDAYA - Untung Kumorohadi (Faculty of Economics and Business Universitas Jenderal Soedirman, 2014)
Goals and specific targets of IBM's activities are: 1) Increased knowledge,abilities and skills to make batik. 2) Increasing the knowledge, abilities and skills inbatik dyeing process. 3) Have an equipment to support the production and displaytourist attraction to tourists who visiting blandhongan. 4) Increasing the ability to addvalue to thebatik products into a fashion product or a variety of other craft products. 5)Increased tourism human resource competence so that partner can provide a goodservice to tourists who visit Kampung Batik Sokaraja Kulon.The activities in this IbM program include; 1) Training of batik makingtechniques, 2) Training of batik dyeing technique, 3) Training to make craft product toan increase value-added of batik products, 5) Introductions and transfer technology inthe form of sewing machines and machine obras , 6) Counseling and advocacy efforts toincrease tourism HR competence,.The outcomes of this program 1) A good quality of batik product with differentdesign and color, 2) appropriate technology (sewing machine and machine obras) tosupport production process, 3) batik crafts which have higher the value added productsof batik; 4) a better quality of human resources tourism